Meugang Tradition of Aceh Society from the Perspective of Hadith: An Analysis of Social and Religious Values in Shaping Communal Life - Siregar, Khoirun Nisa; Munandar, Munandar (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
The Meugang tradition is a cultural heritage of the Acehnese people, held before Ramadan, Eid al-Fitr, and Eid al-Adha. The main activities involve the slaughtering of animals and the mass cooking of meat as an expression of gratitude and preparation for the arrival of these significant Islamic holidays. This tradition not only reflects social and cultural values but is also closely tied to religious aspects believed to be rooted in Islamic teachings. This study aims to analyze the implementation of the Meugang tradition in Mata Ie, Darul Imarah District, Aceh Besar Regency, from a hadith perspective to assess the alignment of its values with Islamic principles. The study employs a qualitative-descriptive method using the living hadith approach and taḥlīlī analysis. The findings reveal that the Meugang tradition has a strong foundation in Islamic teachings, particularly hadiths regarding the encouragement of sharing food, welcoming festivals with joy, and the importance of strengthening social bonds. Although this tradition is not explicitly mentioned in the hadith, the values contained within it align with the spirit of the teachings of the Prophet Muhammad. The implications of this research emphasize that the preservation of Meugang can strengthen Islamic values in social life, maintain religious cultural identity, and serve as an example of harmonizing local wisdom with religious teachings.